A linguagem na esquisofrenia: uma questão de lugar - Macêdo, Luciana Enilde de Magalhães Lyra (2010)
In a psychoanalytic perspective, schizophrenia corresponds to one of the possibilities of psychic structures situated in the field of the psychosis. The language's peculiarities in the schizophrenia identified in the clinic, such as: the references to a shattered body, the fragmentation of the speech, and especially the use of the third person to make a reference to ownself, they send us to extremely archaic questions of the process of psychic constitution. From which place is possible to the subject to produce discursive addressings and to situate himself in the world? In other words, what does disable a subject to address the word in proper name? These questions were taken as a direction to this research, whose purpose was to study the language in schizophrenia linked to questions related to the addressing between mother and child, as well as, to the constitution of the subject considering the beginning of his relationship with the Other the Other of the language, an anchorage place for the subject. For this, we have used the development of the clinic case in the psychoanalytic research, that emphasizes the subject s localization and his productions through his speech. In a tentative of a dialogue between the theory and the clinic, we worked with the clinical case of João, who with his speech introduces the singular in the universal, making us reflect about the specificity of a clinic that emphasizes the subject s word. Therefore, considering that the subject s structure discloses itself in the own saying, starting from João s speech, we interrogated the consistence of the Other in schizophrenia, in which there is a connection with the mother s desire and with the Name-of-Father . In addition to this, we discussed the clinical interventions and the possibility of inscription of a place less deadly in front of the Other